A responsabilidade civil em decorrência de acidentes envolvendo veículos semiautônomos à luz da teoria geral dos deveres fundamentais - Barbosa, Bruna Sabadini Pagotto (2024)
The current automobile industry is experiencing the “new gold rush” regarding the production and commercialization of increasingly technological vehicles, mainly to increase the driver's well-being and make traffic a safer and more sustainable environment. Among the innovations and investments made, is important to mention the development of semi-autonomous vehicles, that have partial driving automation that do the driving task partially, through sensors, cameras, software and hardware, not dismissing the presence of the driver. However, even though the companies that develop these cars promise a safer technology, such vehicles are not exempt from being involved in accidents, which makes it necessary to study the damage caused and its compensation. This dissertation seeks to study the incidence of civil liability in cases of damage involving semiautonomous vehicles and to answer the following research problem: in light of the theory of fundamental duties, who is assigned the duty to repair the damage caused in accidents involving vehicles with level 2 autonomy, or semi-autonomous vehicles? During this analysis, the fundamental duty of traffic safety and the principle of solidarity will be studied, as well as the institute of civil liability of the manufacturers and drivers of these vehicles. Through a study in the theoretical and speculative field, using the deductive method and having as a theoretical basis the theory of fundamental duties and the theory of civil liability, it will be possible to answer that, in case of failure in the driving automation system, the vehicle manufacturer will objectively respond for the damage caused. In the case of fault on the part of the driver, he will be subjectively liable for the damage caused, applying the theory of presumed guilt. The obligation of these agents consists from the fundamental duty of traffic safety and solidarity. The relevance of this work lies in the need to study this new technology that is already being commercialized in the market, given the lack of specific legislation on this matter